Knowledge of Internet Technology and Its Application System in the Perspective of Islamic Economics Interest in Online Shopping - Adriansah, Adriansah; Uswatun Hasanah, Hana (Muttaqien, 2023)
This research was conducted to determine the effect of knowledge of internet technology and application systems partially or simultaneously on the online shopping interest of the community in the Bumi, Gandasari housing estate, Babakancikao District, Purwakarta Regency. This study uses a quantitative approach method. The sample taken is 55 people. The analysis technique used is the partial test, multiple linear regression test, and the coefficient of determination. The results show that knowledge of internet technology and application systems partially or simultaneously has a positive and significant effect on Online Shopping Interest. This is evidenced by the results of a partial test on knowledge of internet technology resulting in a t count > t table (2.645> 2.007), while the significance value is < 0.05 (0.013 <0.05). In the application system obtained t arithmetic > t table (3.170> 2.007), while the significance value <0.05 (0.004 <0.05). The results of the multiple regression test on Online Shopping Interest obtained f count > f table (19.452>3.18), while the significance value <0.05 (0.001 <0.05). Based on the coefficient of determination test, the Adjusted R square value is 0.606. Then the magnitude of the influence of knowledge of internet technology and application systems simultaneously is 60.6%.